Work Values and the Value of Work: Different Implications for Young Adults' Self-Employment in Europe. Issue 1 (March 2019) - Lukeš, Martin; Feldmann, Manuel; Vegetti, Federico
In this study, we ask how work values impact different forms of labor market participation of young adults across Europe. We define work values as individuals' intrinsic and extrinsic motivations to work and the value of work as the importance or centrality of work in individuals' lives. We use data gathered from young adults in eleven European countries in the CUPESSE project to investigate the role of the two sets of values regarding employment and self-employment. We then replicate our analysis on a larger sample using data from the European Social Survey (ESS). Our findings suggest a high importance of nonpecuniary benefits for self-employment. Analyses based on both CUPESSE and ESS datasets clearly showed the high, positive impact that independence and creativity have on self-employment. We also show that extrinsic values, such as job security, are more important for employees than they are for the self-employed. Additionally, we find that the value of work in life does not differ between the employed and the self-employed. In sum, these findings suggest that values related to self-employment are not rooted in a general value of work, as Max Weber postulated in his Protestant Work Ethic nearly one hundred years ago, as much as in the aim to achieve personal satisfaction.